Federal Minimum Wage Laws and the Employment of Minority Youth - Betsey, Charles L.; Dunson, Bruce H. (American Economic Review, 2016)
Numerous studies have emerged over the past decade dealing with the employment effects of minimum wage legislation (for example, see Jacob Mincer and Edward Gramlich). These studies uniformly show that some amount of disemployment results from the imposition of a minimum wage above a wage that would prevail in the absence of such legislation; though there is considerable dispute concerning the magnitude of the effect. In addition, most if not all of the recent studies indicate a greater employment sensitivity to changes in the minimum wage on the part of teenagers, nonwhites, and the low-skilled, generally, than is true for other groups. Job losses due to higher minimum wages may contribute to high unemployment rates among youth in general, and minority youth in particular. This paper presents no direct evidence on the impact of the minimum wage on teenage unemployment. Its results do suggest, however, that previous studies of the impact of the minimum wage on employment loss were probably biased towards overstatement of the effect of the minimum wage. In the case of nonwhite teenagers, the results presented here indicate that over the period 1954 to 1979, cyclical factors affected nonwhite teenage employment to a far greater extent than did changes in the minimum wage.